Attitude Toward Mathematics of Future Teachers: How Important Are Creativity and Cognitive Flexibility? - de-la-Peña, Cristina; Fernádez-Cézar, Raquel; Solano-Pinto, Natalia (Frontiers in Psychology, 2021)
The attitude toward mathematics is shaped by cognitive components such as beliefs and cognitive processes. However, the importance of cognitive processes in attitude toward mathematics has not yet been researched. Therefore, this study aimed to identify the role of cognitive processes, creativity and cognitive flexibility, in the attitude toward mathematics of future teachers. For that purpose, 218 University students and preservice teachers, completed assignments on creativity and cognitive flexibility and a questionnaire on attitude toward mathematics. The results showed that the use of innovative details (a creativity subscale) rises the probability of exhibiting a positive attitude toward mathematics by 1.81. Besides, cognitive flexibility rises this probability by 2.32. The conclusion is that both, details and cognitive flexibility act as good predictors of a positive attitude toward mathematics. This has implications for educational practice in the planning of mathematics instruction in higher education, specifically, in future teachers.